Predation of Picus canus Gmelin JF, 1788 (Grey-headed Woodpecker) by Accipiter nisus (Linnaeus, 1758) (Eurasian Sparrowhawk) in Chail Wildlife Sanctuary, Himachal Pradesh, India - Sanjeev Sharma; Rakeshwar Kapoor (Journal of Fauna Biodiversity)
The observation of predation on Picus canus in the Western Himalayas is noteworthy and adds to the limited documentation of such events in this region.